1999
DOI: 10.2135/cropsci1999.0011183x003900020014x
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis of Gene Effects Conditioning Resistance to Stagonospora nodorum (Berk.) in Wheat

Abstract: Stagonospora nodorum (Berk.) blotch (SNB) is a fungal disease that affects all aboveground parts of wheat (Triticum aestivum L.) plants. Stagonospora nodorum blotch causes serious losses in grain yield and seed quality of wheat grown in the southeastern USA. The objective of this study was to conduct a genetic analysis of components of partial resistance to SNB in wheat. Ten lines of soft and hard winter wheats that varied in resistance to SNB were used in two sets of intrawheat‐class half‐diallel matings. See… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…Some previous findings (Duguid and Brûlé-Babel 2001;Singh et al 2006) differed from our results because most wheat genotypes susceptible to the fungus were sensitive to the Ptr ToxA. Although resistance to SNB has been reported to be controlled by multiple genes (Bostwick et al 1993;Du et al 1999;Fried and Meister 1987;Liu et al 2004;Scott et al 1982) or by single genes (Ma and Hughes 1995;Murphy et al 2000), resistance breeding that combines seedling stage resistance and adult plant resistance has been suggested to be more durable to SNB (Krupinsky et al 1972). Our study was conducted to evaluate artificially-inoculated seedling stage in the greenhouse.…”
Section: Discussioncontrasting
confidence: 56%
“…Some previous findings (Duguid and Brûlé-Babel 2001;Singh et al 2006) differed from our results because most wheat genotypes susceptible to the fungus were sensitive to the Ptr ToxA. Although resistance to SNB has been reported to be controlled by multiple genes (Bostwick et al 1993;Du et al 1999;Fried and Meister 1987;Liu et al 2004;Scott et al 1982) or by single genes (Ma and Hughes 1995;Murphy et al 2000), resistance breeding that combines seedling stage resistance and adult plant resistance has been suggested to be more durable to SNB (Krupinsky et al 1972). Our study was conducted to evaluate artificially-inoculated seedling stage in the greenhouse.…”
Section: Discussioncontrasting
confidence: 56%
“…Several genetic studies have shown resistance to SNB to be controlled by multiple genes (Bostwick et al 1993;Du et al 1999;Wicki et al 1999a). Liu et al (2004a, b) reported a major QTL accounting for 58% of the phenotypic variation in the ITMI mapping population.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of genetic studies (Bostwick et al 1993;Du et al 1999;Ecker et al 1989;Fried and Meister 1987;Nelson and Gates 1980;Scott et al 1982;Wicki et al 1999b) reported that the genetic basis of resistance to SNB in wheat is quantitatively inherited. Resistance loci against SNB were mapped on 16 of the 21 wheat chromosomes (Nicholson et al 1993;Hu et al 1996;Liu et al 2004bLiu et al , 2006Xu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To establish effective F 1 hybrid breeding programs, genetic information such as the combining abilities and heritabilities of important plant characteristics must be known. Although numerous analyses of combining ability have been reported for important agronomic traits such as yield (Rainey & Griffiths, 2005) and disease resistance (Du et al, 1999) in edible crops, few studies have investigated the combining abilities of flower appearance characteristics in floricultural crops, with the exception of flower longevity (Van der Meulen-Muisers et al, 1999;Krahl & Randle, 1999).…”
Section: Introductionmentioning
confidence: 99%